Development of the Experimental Stand for Studying and Testing Digital Protection Terminals - Shabovta M.; Besarab O.; Plis V. (Problems of the Regional Energetics)
However, the approach to designing laboratory stands for training students and electrical per-sonnel on the specifics of using digital protections in most cases has remained the same, which does not allow for fully realizing their potential. The purpose of the work is to improve the qual-ity of the knowledge and practical skills received by students in the work with digital protection blocks. To achieve the goal, a specialized laboratory stand for testing digital security terminals has been developed. The stand consists of a mathematical model of the protected object, imple-mented in the form of a computer program and hardware, which allows real-time conversion of changes in model mode parameters into physical signals transmitted to the digital protection de-vice. The stand provides the terminal feedback with the model, which makes it possible to study the protection behavior in the characteristic operating modes of the protected element. The pro-tection of the "line-transformer" block using the Siprotec 4 7SJ6 Siemens terminal is considered. It is possible to calculate the protection operation parameters, configure the digital protection device, and also check the correct operation of the protections by automatically simulating nor-mal and emergency operation modes of the protected object. The software and hardware of the stand makes it easy to expand its capabilities by adding new models of power system objects and other digital protection devices. The equipment used in the developed stand does not require significant capital investments, which makes this approach accessible to higher educational insti-tutions.